SoxD transcription factor deficiency in Schwann cells delays myelination in the developing peripheral nervous system - Ittner, Ella; Hartwig, Anna; Elsesser, Olga; Wüst, Hannah; Fröb, Franziska; Wedel, Miriam; Schimmel, Margit; Tamm, Ernst R.; Wegner, Michael; Sock, Elisabeth (Scientific Reports, 2021)
The three SoxD proteins, Sox5, Sox6 and Sox13, represent closely related transcription factors with important roles during development. In the developing nervous system, SoxD proteins have so far been primarily studied in oligodendroglial cells and in interneurons of brain and spinal cord. In oligodendroglial cells, Sox5 and Sox6 jointly maintain the precursor state, interfere with terminal differentiation, and thereby ensure the proper timing of myelination in the central nervous system. Here we studied the role of SoxD proteins in Schwann cells, the functional counterpart of oligodendrocytes in the peripheral nervous system. We show that Schwann cells express Sox5 and Sox13 but not Sox6. Expression was transient and ceased with the onset of terminal differentiation. In mice with early Schwann cell-specific deletion of both Sox5 and Sox13, embryonic Schwann cell development was not substantially affected and progressed normally into the promyelinating stage. However, there was a mild and transient delay in the myelination of the peripheral nervous system of these mice. We therefore conclude that SoxD proteins—in stark contrast to their action in oligodendrocytes—promote differentiation and myelination in Schwann cells.
CRIS-Team Scopus Importer:2021-07-16